Christian Contribution To Tamil Literature - Dr.M.MAARAVARMAN1 , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Christian missionaries studied Tamil language in order to propagate their religion. Henrique Henrique’s, Nobili, G.U. Pope, Constantine Joseph Beschi, Robert Caldwell, Barthalomaus Zieganbalg, Francis Whyte Ellis, Samuel Vedanayagam Pillai, Henry Arthur Krishna Pillai, Vedanayagam Sastriyar, Abraham Pandithar had been the Christian campaigners and missionaries. Pope was along with Joseph Constantius Beschi, Francis Whyte Ellis, and Bishop Robert Caldwell one of the major scholars on Tamil. Ziegenbalg wrote a number of texts in Tamil he started translating the New Testament in 1708 and completed in 1711.They performed a remarkable position to the improvement of Tamil inclusive of the introduction of Prose writing.Christian Priest understood the need to learn the neighborhood language for effective evangelization. Moreover, they centered on Tamil literature in order to recognize the cultural heritage and spiritual traditions. The Priest learnt Tamil language and literature with an agenda and no longer out of love or passion or with an intention of contributing to the growth of the language.Tamil Christian Literature refers to the various epic, poems and other literary works based on the ethics, customs and principles of Christian religion. Christians both the catholic and Protestant missionaries have also birthed literary works. Tamil-Christian works have enriched the language and its literature. Thorough the variety and quality of classical Tamil literature, Tamil language is described as the great classical traditions and literatures of the world.In 2004, the government of India declared Tamil language as classical language.